The cultural diversity of European unity : findings, explanations and reflections from the European values study - Arts, Wilhelmus Antonius, 1946-; Hagenaars, Jacques A.; Halman, Loek (European values studies (Leiden, Netherlands) ;, 2003)
This work deals with the values of the people in contemporary Europe. Using the survey data from the European Values Study, a number of basic values and the dynamics of value change are explored from an economic, political, social, and religious-moral point of view.